Changes in nutrient stoichiometry: phytoplankton & organic matter dynamics in coastal upwelling systems - Meyer, Judith (2016)
Coastal upwelling systems associated to the eastern continental margins of the Atlantic and Pacific Oceans are among the most productive realms of the marine ecosystems. Although they only occupy a small area, they play a globally important role in the cycling of nitrogen (N), phosphorus (P) and other biologically relevant elements. In subsurface waters of upwelling systems, oxygen minimum zones (OMZs) persist as a result of biological degradation and sluggish ventilation. Reduced oxygen concentrations influence redox sensitive nutrient inventories by promoting N loss processes and P release from the sediment. Hence, water masses upwelled to the surface feature low N:P ratios that deviate from canonical Redfield proportions of 16:1. Due to the excess P over N, upwelling systems are thought to favor the growth of dinitrogen (N2) fixing organism (diazotrophs) that could potentially restore inorganic nutrient ratios back to Redfield proportions and replenish the N deficit in those waters. Contrary to this assumption, the presence of nondiazotrophic phytoplankton utilizing nutrients in lower than Redfield proportions has been suggested to eliminate the niche for diazotrophs. Thus, the dominance of either Redfield or non-Redfield primary production is thought to determine the amount of N fixed in upwelling systems. In light of expanding OMZs and the predicted modification of nutrient inventories, this doctoral dissertation aimed to investigate the impact of changing N:P supply ratios on phytoplankton and organic matter composition. Moreover, the potential of primary producers to modify nutrient supply anomalies and their role in coupling or decoupling sources and sinks of fixed N was assessed. To accomplish this, nutrient manipulation experiments and a field study were conducted in the eastern tropical North Atlantic (ETNA) and eastern tropical South Pacific (ETSP).